Persistent fluid flows defined by active matter boundaries - Zijie Qu (Nature Portfolio, 2021)
Controlling active matter represents an exciting avenue for studying collective pattern formation. In this article the authors present optical control of persistent flows of active filaments-motor protein mixtures and show how boundaries determine the architecture of active flows